The study of comparative impact of an integrated model (GSR: Grandstand, Supervising and Report-back) versus SNAPPS of outpatient education on developing students' clinical competencies in Infectious clerkship - Khaironnesa Ramazanzade; Azadeh Ebrahimzadeh; Ali Nazeri (Mashhad University of Medical Sciences, 2024)
Background: This study aimed to compare the effectiveness of  SNAPPS and an integrated model of outpatient education in developing clinical competencies of clerkship students concerning infectious diseases.Method: This study has a quasi-experimental design (pretest, posttest, control group). The experimental and control groups were selected without random placement. The experimental group was trained using the integrated model, whereas the controls were trained with the SNAPPS model. After the data were collected, the test results were analyzed  in the three areas of Knowledg, clinical reasoning, and skills using the Wilcoxon test, Mann-Whitney U test, and paired t-test.Results: The mean within-group score changes were significant in both groups concerning clinical reasoning, skills, and cognition. The cognition mean scores in the integrated and SNAPPS models were 18.94 and 18.06, respectively, with a significant difference between the two models (P=0.029). However, there were no significant differences between the groups concerning the mean scores of clinical reasoning (p=0.425) and skills (p=0.092).Conclusion: The integrated model outperformed SNAPPS in increasing the knowledge, clinical reasoning,and skills of clerkship students.